Probing the limits of tool competence: Experiments with two non-tool-using species (Cercopithecus aethiops and Saguinus oedipus) - Santos, Laurie R.; Pearson, Heather M.; Spaepen, Geertrui M.; Tsao, Fritz; Hauser, Marc D. (Animal cognition, 2006)
Non-human animals vary in their ability to make and use tools. The goal of the present study was to further explore what, if anything, differs between tool-users and non-tool-users, and whether these differences lie in the conceptual or motor domain. We tested two species that typically do not use tools-cotton top tamarins (Saguinus oedipus) and vervet monkeys (Cercopithecus aethiops)-on problems that mirrored those designed for prolific tool users such as chimpanzees. We trained subjects on a task in which they could choose one of two canes to obtain an out-of-reach food reward. After training, subjects received several variations on the original task, each designed to examine a specific conceptual aspect of the pulling problem previously studied in other tool-using species. Both species recognized that effective pulling tools must be made of rigid materials. Subsequent conditions revealed significant species differences, with vervets outperforming tamarins across many conditions. Vervets, but not tamarins, had some recognition of the relationship between a tool's orientation and the position of the food reward, the relationship between a tool's trajectory and the substance that it moves on, and that tools must be connected in order to work properly. These results provide further evidence that tool-use may derive from domain-general, rather than domain-specific cognitive capacities that evolved for tool use per se.